Vienna 1814 how the conquerors of Napoleon made love, war and peace at the Congress of Vienna - King, David (Harmony Books, 2008)
Details the 1814 Congress of Vienna, offering portraits of the participants and discussing the political intrigues, illicit affairs, tangled alliances, and bitter rivalries that marked the occasion that transformed the face of nineteenth-century Europe.
Includes bibliographical references and index
Keywords: Congress of Vienna / (1814-1815); Congress of Vienna -- (1814-1815); Wiener Kongress -- 1814-1815 -- Wien; Geschichte 1800-1900; Napoleonic Wars, 1800-1815 / Treaties; Statesmen / Europe / History / 19th century; Geschichte; Politik; Napoleonic Wars, 1800-1815 -- Treaties; Statesmen -- Europe -- History -- 19th century; Europe / Politics and government / 1789-1815; Europa; Europe -- Politics and government -- 1789-1815